2021
DOI: 10.1002/cnma.202100385
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution in P2‐type Layered Oxide Cathode Materials for Sodium‐Ion Batteries

Abstract: Sodium‐ion batteries (SIBs) have attracted much attention due to their abundance, easy accessibility, and low cost. P2‐type layered oxide materials, as one of the most potential cathode candidates for SIBs, have been widely studied. However, various kinds of structural evolution during cycling are harmful to the stability. In the present Minireview, the phase transitions occurring in the process of charge/discharge are summarized, and the mechanism of structural rearrangement and phase transition are introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Compared with the O3-type material, the P2-type Na x TMO 2 has a more stable structure and higher ionic conductivity. 20–22…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the O3-type material, the P2-type Na x TMO 2 has a more stable structure and higher ionic conductivity. 20–22…”
Section: Introductionmentioning
confidence: 99%
“…The internal factors affecting the structural evolution of layered oxides are the number and distribution of sodium-ions within the lattice. 46 Arcelus et al 47 developed a model system using density functional theory calculations to examine the Pn ↔ On transition from an atomic point of view and confirmed that the sliding-driven P → O transition might be successfully prevented at high Na content. The structural evolution during sodium-ion de-embedding can be verified by ex situ XRD tests in different charge and discharge states.…”
Section: Fundamental Understanding Of O3-type Layered Transition Meta...mentioning
confidence: 95%
“…The electrochemical characteristics of the cathode material affect the electrochemical characteristics of the whole battery. The theoretical energy density of the cathode material is the upper limit of the energy density of the battery cell, and the cathode material affects the power density of the SIBs by affecting the ability to accommodate sodium ions and the fluency of the transmission channel [69–71] . At the same time, the loss of active substances in the cathode material and the impurity composition will affect the life of the battery.…”
Section: Sodium‐ion Batteries Electrode Materialsmentioning
confidence: 99%